The influence of the trust on customer satisfaction in mobile phone market: An empirical investigation of the mobile phone market - Al-Refai, Abdalla Nayef; Mohd Noor, Nor Azila (Society of Scientific Research and Education (SSRE), 2014)
This paper focuses on the impact of trust on customer satisfaction in mobile phone sector.In order to examine the relationship between independent variable (trust) and dependent variable (customer satisfaction), SPSS and Smart (PLS) have been used.For the purpose of this study, the data was gathered from mobile phone subscribers.Out of 113 questionnaires distributed, number of usable questionnaires received back was 103.The results of the study regarding to the impact of independent variable and dependent variable of mobile phone was reinforced in absolute conformity with the resource based view of the past researches that considers the customer satisfaction as a determining factor behind competitive advantage and long term success. The findings of this study have substantiated the significant impact of trust on customer satisfaction in mobile phone market.The paper concludes to Discussion, Limitation as well as future research insights and venues for the upcoming researchers to explore.